OFR-96-76 Evaluation Of Speech Processing Systems - Evaluation Of Electronic/Active Hearing Protectors For Use In Underground Coal Mines - Paul L. Michael (The National Institute for Occupational Safety and Health (NIOSH), 1976)
This report presents a discussion of perforance parameters for electronic or active hearing protectors that will meet the needs of underground coal miners. This information is incorporated into a proposed set of specifications that can be used to judge the suitability of a particular electronic hearing protector for the coal mine application. Acoustic and electrical tests were performed on a developmental model of an electronic hearing protector built by the U. S. Bureau of Mines. This model showed only a slight reduction in speech intelligibility which was traced to poorly matched components and in particular to the transducers. Tests of alternative components showed the Knowles BL-1671 microphone to be suitable for this application because of its performance and extremely small size. The Roan-well H-143/AIC earphone was found to have a good frequency response but has the disadvantage of being rather bulky which causes a slight degradation of a low frequency attenuation of the hearing protector. A satisfactory installation of these components in a hearing protector muff was demonstrated and tested. Results of tests of several methods of controlling the sound level under the hearing protector muff showed that a simple diode clipper circuit can be used with only a negligible loss in speech intelligibility for normal-hearing listeners. A commercially available active hearing protector, the British-built ACOS A-9000/2 was examined. This hearing protector provides sound level limiting through a saturating amplifier. Preliminary tests have shown that the performance characteristics of this commercial unit meet many of the proposed specifications so further testing and evaluation should be performed to determine its suitability for use 1n underground coal mines. The recommended test of intelligibility for electronic hearing protectors and other communication systems as used in a coal mine setting is the Modified Rhyme Test (MRT) developed by House et al. in 1965. The suitability and method of administering this test are discussed.